PENERAPAN TEKNOLOGI BIOCHAR BERBASIS KARBON OFFSET MENGGUNAKAN TONGKOL JAGUNG PADA KELOMPOK TANI MASSEDDI I KABUPATEN WAJO - Sukmawati, Sukmawati; Rahim, Iradhatullah; Bahruddin, Bahruddin; Suherman, Suherman; Yamin, Mayasari; Qadri, Sri Nur; Zamzam, Syamsiar; Fatmawati, Fatmawati (Departemen Budidaya Pertanian Fakultas Pertanian UNHAS, 2024)
Limbah pertanian merupakan sumber bahan organik berkelanjutan di dunia. Untuk mengatasi penurunan kesuburan tanah yang berkepanjangan, lahan pangan membutuhkan penambahan bahan organik secara berkelanjutan. Biochar merupakan bahan organik yang persisten tersimpan dalam tanah. Tujuan kegiatan ini adalah untuk meningkatkan wawasan petani dalam memanfaatkan teknologi biochar tanpa asap dalam mengelola tongkol jagung sesuai prosedur karbon kredit. Metode pelaksanaan kegiatan terdiri dari: 1) Training prosedur standarisasi; 2) Produksi biochar dan pupuk slow release; dan 3) Aplikasi biochar sebagai bahan pembenah tanah. Hasil dari kegiatan ini adalah: 1) Meningkatnya kemampuan kelompok tani memproduksi biochar sesuai prosedur karbon kredit; 2) Sertifikasi biochar untuk kelompok tani; dan 3) Meningkatnya kandungan C-organik tanah. Dalam kegiatan ini melibatkan 40 orang anggota Kelompok Tani Masseddi I yang berkomitmen untuk mengolah limbah jagung menggunakan teknologi biochar sesuai prosedur karbon kredit sebagai tindak mitigasi petani jagung menghadapi perubahan iklim. ABSTRACT Agricultural waste is a source of sustainable organic matter in the world. To overcome the prolonged decline in soil fertility, food fields require the addition of organic matter on an ongoing basis. Biochar is a persistent organic material stored in the soil. This activity aims to increase farmers' insight into utilizing smokeless biochar technology in managing corn cobs according to the carbon credit procedure. Methods in implementing activities consist of 1) Standardization procedure training, 2) Biochar and slow-release fertilizer production, and 3) Application of biochar as a soil amendment. The results of this activity are: 1) Increasing the ability of farmer groups to produce biochar according to carbon credit procedures; 2) Biochar certification for farmer groups; and 3) Increasing soil C-organic content. This activity involved 40 Masseddi I Farmer Group members committed to processing corn waste using biochar technology according to the carbon credit procedure as a mitigation measure for corn farmers facing climate change. Keywords: Biochar, bioremediation, carbon credits, carbon offset, slow-release fertilizer. ABSTRACT Agricultural waste is a source of sustainable organic matter in the world. To overcome the prolonged decline in soil fertility, food fields require the addition of organic matter on an ongoing basis. Biochar is a persistent organic material stored in the soil. This activity aims to increase farmers' insight into utilizing smokeless biochar technology in managing corn cobs according to the carbon credit procedure. Methods in implementing activities consist of 1) Standardization procedure training, 2) Biochar and slow-release fertilizer production, and 3) Application of biochar as a soil amendment. The results of this activity are: 1) Increasing the ability of farmer groups to produce biochar according to carbon credit procedures; 2) Biochar certification for farmer groups; and 3) Increasing soil C-organic content. This activity involved 40 Masseddi I Farmer Group members committed to processing corn waste using biochar technology according to the carbon credit procedure as a mitigation measure for corn farmers facing climate change. Keywords: Biochar, bioremediation, carbon credits, carbon offset, slow-release fertilizer.